Covid-19, Financial Markets (Islamic vs Non-Islamic), and Exchange Rate: Does the Malaysian Market Offers Diversification Opportunities to the Investors? - Hassanudin Mohd Thas Thaker; K. Chandra Sakaran (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2021)
We explore the impact of Covid-19 towards Islamic and non-Islamic financial markets in Malaysia. We employ the wavelet coherency approach (WCA) which allows a deeper investigation of the relationship between the selected variables in terms time-frequency domain. We document that (i) Islamic capital markets represented by FTSEBMEI and MyETFDJIMMT25 are performing better during the Covid-19 period and also offer a greater investment opportunity to the investors for diversification purposes, (ii) non-Islamic index, FTSEBMKLCI, was less affected during this pandemic, and the market offers better risk and optimal diversification benefits to the investors as time progresses, and (iii) exchange rate appears to be more stable and within the phase category, indicating the co-movements are relatively strong in smaller scales. Understanding the impact of Covid-19 on the financial markets will lend to a better portfolio investment design which considers return and risk.